HIJAB CONTROVERSIES IN NIGERIA - Stella E. Osim (Social Sciences, Humanities and Education Journal (SHE Journal), 2021)
Over the past decade, and particularly since the September 11th terrorist attack in the United State, the Muslim community in most parts of the world has experienced an increased level of social and religious scrutiny. This unfortunate incident has fundamentally changed the way the mostly dominated Muslim society views Muslims, especially Muslim women who wear the veil or hijab in public. Muslim women have experienced various instances of discrimination including people trying to remove their hijab, and/or name-calling. A unique aspect of Muslim women in Nigeria is that they not only confront the stigma of gender, race, ethnicity, and religion but that which is attached to Islamic dress as well. Despite some of these problems, however, the experiences of Muslim women all over the world remain one of the least researched topics in sociology. The purpose of this work is to explore the controversies surrounding the hijab in Nigeria.